The Timeless Value of a Pluralistic World - Valentin Yakushik (International Society of Philosophy and Cosmology, 2018)
The article reproduces a slightly edited author's 'personal manifesto' presented as a paper at a Workshop on the 'Future of World Order' in Tripoli, Libya in May 2003. The present version contains some further thoughts topical in the present time. As originally presented the paper sought to address four major issues: US domination in the newly mono-polar world; the pathologies of international power relations in a world characterised by huge disparities in access to multiple technologies; differing, hierarchically-structured patterns of organising and containing inter- and intra-national conflicts; and the need for moral, political and intellectual leadership in the then Brave New World of US hegemony.